The Impact of Leadership Styles on Employee Engagement and Organizational Growth - Rusilowati, Umi; Sriliasta Bangun, Cicilia; Bennet, Daniel (APTISI Transactions on Management (ATM), 2025)
Leadership plays a crucial role in shaping organizational success by influ- encing employee engagement, motivation, and overall business performance. Effective leadership fosters an environment where employees feel valued, en- gaged, and aligned with corporate goals, ultimately driving sustainable growth. This study aims to analyze the impact of different leadership styles transformational, transactional, and servant leadership on employee engagement and their subsequent effect on organizational growth. By employing a quantitative research approach using Structural Equation Modeling (SEM) with SmartPLS, this study provides empirical evidence on how leadership behaviors affect work- place dynamics. Data were collected from employees across various indus- tries using a structured survey. The relationships between leadership styles, employee engagement, and organizational growth were examined using Partial Least Squares-SEM (PLS-SEM). Reliability and validity were tested through Cronbach’s Alpha, Composite Reliability (CR), and Average Variance Extracted (AVE). The findings indicate that servant leadership has the strongest impact on employee engagement, followed by transformational and transactional lead- ership. Employee engagement significantly mediates the relationship between leadership styles and organizational growth. Organizations should priori- tize transformational and servant leadership approaches to enhance employee engagement and long-term growth. Future research should explore industry- specific leadership adaptations and the role of digital transformation in leader- ship effectiveness.